Ensino Religioso e Formação Docente: uma análise a partir do curso de graduação em Ciências da Religião da Unimontes, no período de 2001 a 2012 - Andrade, Rosana Cássia Rodrigues (2016)
It is noted that the proposed theme has not been sufficiently studied by the Education Science. There is a lack of corresponding teaching degree courses showing the challenging and urgent character of a reflection on the training of Religious Education teachers. This study aims to analyze teachers’ training paradigms that permeate the course of Science of Religion at Unimontes, in order to understand the concepts that underlie the pedagogical proposals in the period of 2001 to 2012. This is a qualitative research with an exploratory study of documentary nature in order to describe the history of the Science of Religion course at Unimontes through the analysis of the Pedagogic Political Project (PPP) elaborated from 2001 to 2012 and official minutes which are part of the educational practices instrumentalized by bibliographic and field researches. The field research used a semi-structured interview which had the participation of 21 professors and 4 coordinators who work or have already worked in the course during this period. In the quantitative data analysis we used the statistical program (Statistical Package for Social Sciences - SPSS) 17.00 for Windows and qualitative data analysis was performed through content analysis technique based on Bardin (2004). The data revealed the importance of the Science of Religion course in an attempt to break solidified paradigms and propose new places and ways of thinking and studying religion. It was also found that the way the PPPs are organized, they emphasize the deepening of specific knowledge of the area, leaving the teacher training under the responsibility of few pedagogical subjects. However, there is an attempt to invest in teacher training to meet the challenge of enabling the professional of Science of Religion, having Science of Religion as a reference area, so the formation of these teachers is still a challenge for educational institutions. This study may give social contribution by showing paths for initial training of RE teachers mainly at Unimontes